Chondroectodermal dysplasia with recurrent lower respiratory tract infections: a case report - Arunkumar, Preethi; Kumaran, C. R. Vignesh (International Journal of Contemporary Pediatrics, 2026)
Chondroectodermal dysplasia (Ellis–van Creveld syndrome), a rare autosomal recessive skeletal dysplasia, is characterized by disproportionate dwarfism, ectodermal dysplasia, polydactyly, and congenital cardiac anomalies. Respiratory involvement is recognized as a contributor to morbidity and mortality, but is under-emphasised. We report a 4-year-old male child born to consanguineous parents presenting with multiple admissions for lower respiratory tract infections (LRTIs) since birth. The physical examination revealed short stature, along with acromesomelic limb shortening, frontal bossing, a depressed nasal bridge, low-set ears, postaxial polydactyly, and dental anomalies. The echocardiogram showed an ostium secundum atrial septal defect. The radiology results showed a restricted thoracic cavity together with shortened rib bones. Through consistent supportive care, the child’s health improved significantly. Currently, he continues to receive treatment from multiple healthcare specialists. This case highlights that recurrent LRTIs are a significant yet under-recognised clinical complication of chondroectodermal dysplasia, underscoring the importance of early respiratory surveillance and multidisciplinary care to improve outcomes.